Reconstruction of tissue-specific protein-protein interaction sub-networks to improve prediction accuracy of bioinformatics tools - Çakır, Nilüfer (My University, 2019)
Biyoinformatik Araçların Tahmin Doğruluğunu Geliştirmek için Dokuya Özgü Protein-Protein Etkileşim Ağlarının Oluşturulması Bu çalışmada dokuya özgü protein-protein etkileşim ağlarının oluşturulması ve system biyotıp uyguşlamalarında performansının gösterilmesi amaçlanmıştır. Bu amaç doğrultusunda, 60 farklı dokuda protein ekspresyon verileri genel insan protein-protein etkileşim ağı ile bütünleştirilerek, her bir dokuya özgü protein-protein etkileşim alt-ağı oluşturulmuştur. Oluşturulan ağlar Cytoscape yazılı ve ilintili alt-programlar ile görselleştirilmiş ve topolojik olarak incelenmiştir. Oluşturulan alt-ağların topolojik analizlerinde derece, aradalık ve yakınlık gibi ağ ölçütleri hesaplanmıştır. Dokuya özgü ağların performanslarının değerlendirilmesinde MATLAB altında çalışan diferansiyel interaktom algoritması kullanılmış ve üç farklı vaka çalışması ele alınmıştır: Meme kanseri, prostat kanseri ve karaciğer kanseri. Hipotezin doğrulanması için, analizler genel protein-protein etkileşim ağı kullanılarak da tekrarlanmış ve sonuçlar karşılaştırmalı olarak incelenmiştir. Prognoz log-rank p-değeri, hazard oranı ve konkordans endeks parametreleri SurvExpress aracı vasıtasıyla hesaplanmış ve performans ölçütleri olarak kullanılmıştır. Performans ölçütlerindeki farklılık ve benzerlikler istatistiksel yaklaşımlar ile gösterilmiştir. Bu çalışmada, dokuya özgü ağların genel protein-protein etkileşim ağına oranla biyoinformatik araçların performansını duruma dayalı olarak iyileştirebileceği gösterilmiştir.

Reconstruction of Tissue-Specific Protein-Protein Interaction Sub-networks to Improve Prediction Accuracy of Bioinformatic ToolsThe presented study was aimed to reconstruct tissue specific protein-protein interaction networks and to demonstrate their performance in systems biomedicine applications. For this purpose, protein expression data for 60 different tissues were integrated with the generic human protein-protein interaction network, and reconstruction of tissue specific protein-protein interaction networks for each tissue was performed. The reconstructed networks were visualized and topologically analyzed using Cytoscape and its plugins. Reconstructed sub-networks were subjected to topological analyses to determine network metrics such as degree, betweenness and closeness metrics. Performance of the tissue specific networks was evaluated using differential interactome algorithm in MATLAB considering three case studies: Breast Carcinoma, Prostate Adenocarcinoma and Liver Cancer. To verify the hypothesis, the analyses were also performed using generic human protein-protein interaction network and the results were comparatively analysed. The prognostic log-rank values, hazard ratio and concordance index parameters were obtained through SurvExpress and employed as the performance metrics. Statistical approaches were used to demonstrate the differences and similarities of the performance metrics. We showed that the use of tissue-specific networks instead of a generic protein-protein interaction network may improve the prediction accuracy of bioinformatics tools in a case-dependent manner.
Keywords: Dokuya Özel Protein-Protein Etkileşimi Tissue-Specific Protein-Protein Interactions Sub-networks